2017
DOI: 10.1007/s00167-017-4685-5
|View full text |Cite
|
Sign up to set email alerts
|

The shape and orientation of the trochlea run more parallel to the posterior condylar line than generally believed

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, our findings are consistent with the current literature analyzing the native knee anatomy. Vercruysse et al described a broad variability between the anterior trochlea line and the TEA, with internal rotation on average [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings are consistent with the current literature analyzing the native knee anatomy. Vercruysse et al described a broad variability between the anterior trochlea line and the TEA, with internal rotation on average [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also believed to favour patellar tracking [10, 17, 21]. Yet, patellofemoral complications after TKA remain common, mainly due to femoral component malpositioning [27]. Newman et al [19] revealed high variability of trochlear rotation in 191 non‐arthritic knees and concluded that the classification of trochlear rotation could yield tailored positioning of the femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, performing TKA in knees of diferent ethnicities can result in considerable mismatches in trochlear parameters. Many surgical approaches for TKA orient the femoral component parallel to the surgical transepicondylar axis (sTEA) [10,17,21] to achieve a balanced lexion gap and externally rotate the posterior condylar axis [27]. This is also believed to favour patellar tracking [10,17,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation